The serum activity of cancer procoagulant in cases of uterine and ovarian neoplasia - Jóźwik, Maciej; Wiśniewski, Ryszard; Dariusz Szajda, Sławomir; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2002)
Cancer procoagulant (CP), a biochemical marker of neoplasia, is an enzyme found in neoplastic tissue and in the blood of patients with malignant diseases. The usefulness of the assessment of CP activity in an oncological diagnosis of female reproductive organs has not been explored. The aim of the present study was to determine the activity of CP in cases of endometrial and ovarian carcinoma, as well as leiomyomas. The CP activities in the serum of patients with these neoplasms were measured by the coagulative method according to Gordon and Benson, and expressed as the coagulation time. We examined 5 patients with endometrial carcinoma, 7 with ovarian carcinoma, and 10 with leiomyomas. The reference group consisted of 11 healthy women. The CP activity in the serum of patients with endometrial and ovarian carcinoma, as well as in cases of leiomyoma was significantly higher (P<0.001) than in the serum of healthy subjects. The results were 55±3.6, 72±10.4, and 161±23.9 s for endometrial carcinoma, ovarian carcinoma and leiomyoma, respectively. In healthy women, this value worked out to be 294±19.2 s. Our evaluation of CP activity indicates an increased level of serum CP in cases of malignant tumors and suggests the applicability of this enzyme in the monitoring of female reproductive organ cancer.